Construction of a Baculovirus Derivative to Produce Linearized Antheraea pernyi (Lepidoptera: Saturniidae) Multicapsid Nucleopolyhedrovirus Genomic DNA. Issue 2 (27th March 2020) - Zhao, Zhenjun; Ye, Bo; Yue, Dongmei; Li, Peipei; Zhang, Bo; Wang, Linmei; Fan, Qi
Abstract: In the Antheraea pernyi multicapsid nucleopolyhedrovirus (AnpeNPV)-based expression vector system, the frequency of homologous recombination events between wild-type AnpeNPV DNA and the transfer vector is low, resulting in a small amount of recombinant virus. Previous reports have indicated that linearized baculovirus DNA can increase the proportion of recombinant virus relative to the total progeny. To improve the recombination efficiency, we constructed a linearized derivative of AnpeNPV, referred to as AnpeNPV PhEGFP -Avr II, in which egfp flanked by Avr II restriction sites was located at the polyhedrin locus and driven by the polyhedrin promoter. Linear AnpeNPV DNA was obtained by the treatment of AnpeNPV PhEGFP -Avr II genomic DNA with Avr II endonuclease. The infectivity and recombinogenic activity between the linearized and circular viral DNA were evaluated by quantitative real-time polymerase chain reactions. We demonstrated that the linearized AnpeNPV DNA produced only small numbers of infectious budded viruses, accounting for approximately 4.5% of the budded virus production of wild-type AnpeNPV DNA in A. pernyi pupae. However, the linearized AnpeNPV DNA substantially increased recombinant virus production after cotransfection with an appropriate transfer vector; relative abundance of the recombinant virus was approximately 5.5-fold higher than that of the wild-type AnpeNPV DNA in A. pernyi pupae. The linearization of AnpeNPV DNA will facilitate the purification of recombinant viruses using the AnpeNPV-based expression vector system and the construction of an AnpeNPV-based bacmid system.